AN EXPLORATORY STUDY ON TURKISH EFL PRE-SERVICE TEACHERS' SUBJECTIVE WELLBEING - (:unkn) unknown (INST PEDAGOSKA ISTRAZIVANJA, 2021)
Subjective well-being (SWB) has been an intensely studied domain of psychology, predominantly in the field of positive psychology. Due to the nature of teaching as an intellectually, physically and emotionally demanding profession, the last few decades have also witnessed a growing interest in teachers' SWB. The present study investigated preservice teachers' (PTs) SWB and explored its relationship to teaching efficacy beliefs and occupational anxiety. A total of 261 PTs enrolled in English Language Teaching departments of five different universities in Turkey participated in the study. Data came from the scales of SWB, teachers' self-efficacy beliefs and occupational anxiety. The findings indicated that PTs had a high level of perceived SWB; female PTs had a significantly higher level of SWB than male ones; PTs' academic year and the type of university they were enrolled in had no significant relationship with their SWB; and both self-efficacy beliefs and occupational anxiety served as significant predictors of PTs' SWB, together explaining 16.2% of the variance in their scores.
Keywords: Subjective wellbeing; self-efficacy beliefs; occupational anxiety; pre-service teachers; English as a foreign language (EFL); POSITIVE PSYCHOLOGY; SELF-EFFICACY; STUDENTS; HAPPY; COMPETENCE; PREDICTORS; SCIENCE; BURNOUT